Políticas públicas de inovação e o processo de incubação de empresas no município de Pato Branco - Colferai, Lucas (2023)
The main objective of this research was to evaluate the contribution of public innovation policies and the incubation processes of technology-based companies in the municipality of Pato Branco, from 1997 to the end of 2022. This trajectory of 25 years of business incubation was consolidated within a local socioeconomic development strategy through Science, Technology and Innovation as a production factor. From this context, from the dynamism that can be observed in the strategies of incubation environments and the third generation of technological incubators, one can see the importance of analyzing the incubation environments in the municipality. Thus, exploratory research was developed from a case study, with documentary research techniques and semi-structured interviews, with the collection of data from primary and secondary sources. In the first phase, a historical documentary survey was carried out on the creation and evolution of incubation environments. In the second phase, documents of the incubation processes were analyzed, seeking to collect data for the research. It was found that 117 companies went through the incubation processes, with the graduation of 19 companies over the years, most of which consolidated in their market segments. In the third phase, interviews were conducted with three profiles of actors in the incubation processes: graduates, non-graduates and incubator managers. From the perspective of the theoretical model adopted to evaluate the support of incubators, it was identified that they have fulfilled their role of supporting entrepreneurs in the development of aspects of Business Management, considering that these have, in general, a more technical profile in the scope of product development. Another highlighted point refers to Business Connection Networks, indicating that incubators provide important networking support, enabling partnerships and new clients. A characteristic of the incubators in Pato Branco is the important articulation with the various actors of the local innovation ecosystem, perceived in the public notices published, in the articulation of the Municipal Council of CT&I and even in the answers to the interviews. In the fourth phase, the consolidation of the identified data and public policies for local innovation was carried out. State law nº 15.634/07 of fiscal incentive to the electronics and information technology industry, the creation of the Municipal Secretariat of CT&I, the Municipal Council of CT&I and, more recently, the municipal law nº 5.942/22 that creates the Policy, the System, the Plan and the Municipal Fund for ST&I in Pato Branco. This set of instruments has helped to strengthen the local innovation ecosystem, promoting coordinated action by local actors, and thus, technology incubators have boosted innovative and technological entrepreneurship.